Leveraging Digital Cooperatives for Inclusive Finance: The Role of Securities Crowdfunding in Achieving the Sustainable Development Goals (SDGs) - Ulum, Kefi Miftachul; Yazid, Azy Athoillah; Ariyanti, Sari; Biantoro, Bagus Rio; Maghfuroh, Nuril Laila; Izzati, Lia Wilda; Ulum, Mohammad Khoirul (SAINTIS Publishing, 2024)
Digital financial innovation has resulted in many financial service products such as crowdfunding. Indonesia legitimised the commercial crowdfunding system through OJK Regulation Number 37 of 2018 on Equity Crowdfunding. The regulation was replaced through OJK Regulation Number 57 of 2020 concerning securities crowdfunding and added to streamline technical matters through OJK Regulation Number 16 of 2021. At the beginning of the regulation, the securities offered were limited to equity types. The change in regulation developed a variety of sukuk and debt securities. In May 2024, sukuk amounted to 105 securities, with a percentage control of 30% of the total 356 securities, consisting of 231 equity and 20 debt. The capitalisation of sukuk increased from the number of sukuk in August 2023, which amounted to 59, with a percentage control of 22% of the total securities. Growth is an opportunity to transform digital-based cooperatives that organise funding in securities crowdfunding services. This opportunity becomes a legal challenge in the aspect of legality, so it is necessary to examine the digital financial innovation to ensure its implementation. Normative legal research is the research method that will be used, collaborating with the statute approach and the conceptual approach as the research approach. Primary data in the form of Law of the Republic of Indonesia Number 17 of 2012 concerning Cooperatives, Law of the Republic of Indonesia Number 20 of 2008 concerning Micro, Small, and Medium Enterprises, and Financial Services Authority Regulation Number 57 of 2020 concerning Securities Offerings Through Information Technology-Based Crowdfunding Services. Secondary data in the form of securities crowdfunding growth and analysed using integrative legal theory with descriptive analysis and descriptive integrative methods. The research found that there is a potential transition of digital-based cooperatives as providers of securities crowdfunding services that have been legitimised through legal integration analysis.